Pelatihan Penggunaan Tool Pembelajaran Daring Yang Efektif Dan Efisien - Ahir Yugo Nugroho Harahap; Adnan Buyung Nst (Insight Power (Kekuatan Wawasan), 2022)
Covid 19 makes all layers of components experience a bad impact, one of which is schools where schools have a very significant impact, one of which is the learning system, which has been using face-to-face learning methods, due to covid 19 the method has changed to an online method. Technological developments should be in line with the development of human resources as technology users. So that the purpose of technology as a tool to help ease human work can be achieved. However, the reality that is happening in Indonesia is that human resources are not completely ready to accept the rapid technological developments. One of them is the number of complaints and obstacles faced by teachers, parents and students themselves in undergoing learning so far. The teacher cannot do the maximum learning, the teacher only gives assignments that are done at home. Students also find it difficult to understand the subject matter and complete the tasks given by the teacher. Parents also experience being overwhelmed with their children because many children are disobedient to their parents, or parents who do not understand the material must study first in order to help their children complete the task. Therefore, training for teachers and students in the use of online media tools is very much needed because there are still many teachers and students who do not understand how to use online tools, where the training includes an understanding of google meet, zoom and google classroom so that teachers and students are able to use the media online to carry out learningKeywords: google meet, zoom, google classroom, online learning, covid 19